Involvement of TLR2, MAPKinase and NFĸβ pathways in regulation of human beta defensin 9 in human corneal epithelial cells stimulated with Pam3CSK4 - Zainal Baharin, Nurul Hana (2017)
Corneal epithelium was shown to provide immune surveillance against invading pathogens through a variety of pathogen recognition receptors (PRR) such as toll like receptors (TLRs) and nucleotide oligomerisation receptors (NLRs) which are capable of recognizing pathogen associated molecular patterns (PAMPs) such as lipopolysaccharide (LPS) and synthetic triacylated lipoprotein (Pam3CSK4), derived from various infection-causing microbes. The elimination of pathogenic microorganisms, including Gram-positive and negative bacteria, fungi and viruses, involves antimicrobial peptides (AMPs). A number of AMPs such as defensins have multiple functions in host defence. Defensins, produced by cells in the course of innate host defence, serve as signals which initiate, mobilise, and amplify adaptive host immune defences. Defensins use multiple cellular receptors, which endow them with the capacity to marshall adaptive host defences against microbial invaders. Human β-defensins (HBDs), one type of defensins family, are an important part of the innate host immune defense at the ocular surface. Unlike other defensins, expression of HBD9, also known as DEFB109, at the ocular surface is reduced during microbial infection, but the stimulation of HCECs by Pam3CSK4 was shown to upregulate HBD9 at the initial responds followed by a significant downregulation. The mechanism of infection or inflammation has been linked with alterations in several important cellular signaling pathways such as TLR2, MAPKinase and NFĸβ pathways. These pathways are of interest from a therapeutic perspective, because targeting them may help to reverse, delay, or prevent inflammation. The main objectives in this study was to determine the involvement of TLR2, MAPKinase and NFκβ signaling pathways in the expression of DEFB109 in Pam3CSK4-stimulated HCECs. The techniques included cell culture stimulated with Pam3CSK4, the exposure of the cells to specific transcription factor inhibitors, qPCR and dot blot analysis. In this study, the evidence to indicate that TLR2 induces HBD9 mRNA and protein expression in a time- and dose-dependent manner was presented. TLR2 siRNA was observed interfering TLR2-mediated induction of DEFB109 expression. The involvement of MAPKinase pathways and NFĸβ pathways in the expression of DEFB109 gene also were observed. These pathway-specific molecules can be exploited to modulate the response of HBD9 during microbial infection. The variable expression of different AMPs to specific pathogens would suggest similar but subtly different pathways invoked by the pathogens, probably related to their PAMPs and different TLRs and other receptors they bind to.